2017
DOI: 10.3847/2041-8213/aa78f7
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Interstellar Using a New Method for High Signal-to-noise HST/STIS Spectroscopy

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. AbstractDue to recent advances in laboratory spectroscopy, the first optical detection of a very large molecule has been claimed in the diffuse interstellar medium (ISM): C 60 + (ionize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
(39 reference statements)
4
35
0
Order By: Relevance
“…The two DIBs increase in this region dominated by UV radiation, as expected for the C 60 molecule ionization and recombination properties. The low ionization potential of C 60 (7.61 eV) favors its ionization in the diffuse medium outside dark clouds, a trend demonstrated by Cordiner et al (2017). Krełowski et al (2015) and have analyzed the 9577 and 9632 Å DIBs in more recent spectra of this star.…”
Section: The 9632 å Dib Toward Hd 37022mentioning
confidence: 85%
See 2 more Smart Citations
“…The two DIBs increase in this region dominated by UV radiation, as expected for the C 60 molecule ionization and recombination properties. The low ionization potential of C 60 (7.61 eV) favors its ionization in the diffuse medium outside dark clouds, a trend demonstrated by Cordiner et al (2017). Krełowski et al (2015) and have analyzed the 9577 and 9632 Å DIBs in more recent spectra of this star.…”
Section: The 9632 å Dib Toward Hd 37022mentioning
confidence: 85%
“…Secondly, weak stellar lines are present in the spectra of the early-type stars used for the DIB detections. In the infrared, their widths and depths can be very similar to those of the DIBs and they may overlap and mimic the weak DIBs (Foing & Ehrenfreund 1994;Cordiner et al 2017;. Finally, additional weak DIBs are also partially blended with the expected bands (Walker et al 2015(Walker et al , 2016(Walker et al , 2017.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Heavy telluric pollution in this wavelength region, particularly by water features, complicates the astronomical data interpretation. As stated earlier, a first attempt to use the Hubble Space Telescope for DIB research in the 1 µm region has been successful (Cordiner et al, 2017), but signals for bands 3, 4, and 5, if any, were found to be at the noise level and a follow up study for different target stars is needed for an unambiguous conclusion. Both C 60 (Cami et al, 2010;Sellgren et al, 2010) and C + 60 (Berné et al, 2013) have been detected in other environments in space through their mid-infrared emission spectra.…”
Section: Resultsmentioning
confidence: 99%
“…As stated before, spectral pollution, mainly due to atmospheric water, severely complicates the analysis of all these ground-based data around 950 nm. For this reason, in another very recent study, Cordiner et al (2017) presented the first Hubble Space Telescope data (i.e., telluric-free) around 1 µm. Several new near-infrared DIBs were reported, but the chosen target star was found to be suboptimal for the DIBs linked to C + 60 .…”
Section: Introductionmentioning
confidence: 99%